Multivariate analysis and its implication in breeding of desired plant type in garden pea (Pisum sativum) - SANWAL, S K; SINGH, B; SINGH, VIKRANT; MANN, ANITA (The Indian Journal of Agricultural Sciences, 2015)
Genetic variance was evaluated in one hundred sixty genotypes of garden pea (Pisum sativum L.) for nine morphological traits through multivariate analysis. Analysis of variance indicated that the genotypes varied significantly among themselves in respect of 9 characters studied. The genotypes were grouped into 14 clusters depending upon their morphological similarity through principal component analysis. Clustering pattern indicated that majority of genotypes, i.e. 113 (70%) were genetically close to each other and grouped in 3 clusters, while apparent diversity was mainly noticed due to 47 genotypes (30%) distributed over 11 clusters. The maximum inter-cluster distance was noticed between III and XIV (61.49) followed by III and VII (51.33) and III and XII (53.27). Considering cluster mean, the genotypes of cluster III might be selected as a suitable parent for future hybridization programme. The contribution of each character towards the expression of genetic divergence indicated that 10-pod weight contributed maximum (58.29) followed by days to 50% flowering (23.83), plant height (11.31) and shelling percent (4.95%). These four characters contributed more than 98% to the total genetic divergence in the genotypes studied.